2021
DOI: 10.1371/journal.pone.0249640
|View full text |Cite
|
Sign up to set email alerts
|

Workplace stress and associated factors among vehicle repair workers in Hawassa City, Southern Ethiopia

Abstract: Introduction Workplace stress is a public health problem worldwide. Studies focusing on work-related stress among vehicle repair workers are scarce in African countries. The current study aimed to determine the prevalence of self-reported workplace stress and associated factors among vehicle repair workers in Hawassa City, South Ethiopia. Methods and findings A cross-sectional study design was employed among 347 vehicle repair workers from January 25 to February 22, 2019. Questionnaires were administered usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Income level and occupational stress are found positive significant relationship. The work stress of low income workers is high whereas high income workers suffer less from work stress ( 43 ). The Tables 6 , 14 also found that the stress level was significantly different among level of education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Income level and occupational stress are found positive significant relationship. The work stress of low income workers is high whereas high income workers suffer less from work stress ( 43 ). The Tables 6 , 14 also found that the stress level was significantly different among level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Another study proved that in garment industry occupational stress are strongly linked to gender ( 42 ), and different hierarchical level of workers like workers suffer from greater work pressure than supervisors. Various studies have shown that occupational stress higher where the work experience is more, Personality factors have shown inclination toward stress ( 43 ). They also revealed stress related to the worker status and showed an association with education level and the occurrence of occupational stress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bei Anstellung von körperlich überdurchschnittlich gesunden Personen für besonders belastende Tätigkeiten, können trotz hoher Belastung in bestimmten Berufsgruppen geringe Erkrankungsraten resultieren. Zudem können durch Möglichkeiten zur vorzeitigen Berentung und Einflüsse von tariflich unterschiedlich vereinbarten Entgeltfortzahlungen im Krankheitsfall Selektionseffekte entstehen [34]. Aber auch arbeitnehmerabhängige interindividuelle Faktoren, wie persönliche Kompetenz und Verantwortlichkeit im ausgeübten Beruf, können einen Einfluss auf die Entstehung von Erkrankungen der oberen Extremität haben.…”
Section: I L I T ä Runclassified
“…Some studies done among healthcare workers revealed that the prevalence of workplace stress ranges from 46.9 to 68.2% [11][12][13]. According to a few studies conducted in Ethiopia to measure the prevalence of work-related stress (WRS) and its determinants among employees of the manufacturing sector showed work-related stress ranged from 40.4 to 45.2% [14][15][16].…”
Section: Introductionmentioning
confidence: 99%